Tuberactinomycin antibiotics: Biosynthesis, anti-mycobacterial action, and mechanisms of resistance - Laughlin, Zane T.; Conn, Graeme L. (Frontiers in Microbiology, 2022)
The tuberactinomycins are a family of cyclic peptide ribosome-targeting antibiotics with a long history of use as essential second-line treatments for drug-resistant tuberculosis. Beginning with the identification of viomycin in the early 1950s, this mini-review briefly describes tuberactinomycin structures and biosynthesis, as well as their past and present application in the treatment of tuberculosis caused by infection with Mycobacterium tuberculosis. More recent studies are also discussed that have revealed details of tuberactinomycin action on the ribosome as well as resistance mechanisms that have emerged since their introduction into the clinic. Finally, future applications of these drugs are considered in the context of their recent removal from the World Health Organization’s List of Essential Medicines.